Frequenz : Journal of RF-Engineering and Telecommunications (De Gruyter, 1949)
The major aim of Frequenz is to highlight current research activities and development efforts in RF/Microwave Engineering, Photonics and Communications across a wide frequency spectrum, from radio and microwave frequencies via THz and infrared to optical frequencies.